Iatrogenic Injury of Profunda Femoris Artery Branches after Intertrochanteric Hip Screw Fixation for Intertrochanteric Femoral Fracture: A Case Report and Literature Review. (5th February 2014) - Patelis, Nikolaos; Koutsoumpelis, Andreas; Papoutsis, Konstantinos; Kouvelos, George; Vergadis, Chrysovalantis; Mourikis, Anastasios; Georgopoulos, Sotiris E.
Abstract : A case of arterial rupture of the profunda femoris arterial branches, following dynamic hip screw (DHS) fixation for an intertrochanteric femoral fracture, is presented. Bleeding is controlled by coil embolization, but, later on, the patient underwent orthopedic material removal due to an infection of a large femoral hematoma.